2022
DOI: 10.2459/jcm.0000000000001343
|View full text |Cite
|
Sign up to set email alerts
|

Preexisting coronary artery disease among coronavirus disease 2019 patients: a systematic review and meta-analysis

Abstract: Aims The prevalence and prognostic implications of coronary artery disease (CAD) in patients infected by the novel coronavirus 2019 (COVID-19) disease remain unclear.Methods We conducted a systematic review and metaanalysis to investigate the prevalence and mortality risk in COVID-19 patients with preexisting CAD. We searched Medline and Scopus to locate all articles published up to December 8, 2021, reporting data of COVID-19 survivors and nonsurvivors with preexisting CAD. Data were pooled using the Mantel-H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 59 publications
(112 reference statements)
0
2
1
Order By: Relevance
“…To note, a few studies do not support the protective role of statins and have shown an association between chronic use of statins with higher mortality and/or morbidity; 29–31 in particular, patients with type 2 diabetes showed the worst outcomes 29,30 . Our study does not support these findings despite the preexisting statin users in the propensity matching score analysis having a higher incidence of diabetes than the statin nonusers (60.1 vs. 56.8%; P -value <0.001).…”
Section: Discussioncontrasting
confidence: 89%
“…To note, a few studies do not support the protective role of statins and have shown an association between chronic use of statins with higher mortality and/or morbidity; 29–31 in particular, patients with type 2 diabetes showed the worst outcomes 29,30 . Our study does not support these findings despite the preexisting statin users in the propensity matching score analysis having a higher incidence of diabetes than the statin nonusers (60.1 vs. 56.8%; P -value <0.001).…”
Section: Discussioncontrasting
confidence: 89%
“…Chronic liver disease is known as an independent risk factor for CDI infection, as well as for COVID-19 infection, due to frequent hospitalizations and reduced immunity [16,42]. It has also been noted that patients with concurrent COVID-19 and CDI have a higher prevalence of essential hypertension (HTN), coronary artery disease (CAD), and congestive heart failure (CHF) [43]. A metaanalysis showed that pre-existing coronary artery disease (CAD) is present in about onetenth of hospitalized patients with COVID-19 [44].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with COVID-19 and concomitant CDI were also observed to have a higher prevalence of essential hypertension (HTN), coronary artery disease (CAD) and congestive heart failure (CHF). A meta-analysis showed that preexisting CAD is roughly present in a tenth of patients hospitalized for COVID-19 [ 11 ]. Similarly, CHF and CAD are overall associated with an increased mortality during active COVID-19 infection [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%